2001
DOI: 10.1177/089686080102100608
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Renal Function in Black South African Patients with Malignant Hypertension: Superiority of Continuous Ambulatory Peritoneal Dialysis over Hemodialysis

Abstract: Objective To describe recovery of renal function (RC) in Black South African patients with primary malignant hypertension (MHT) and end-stage renal failure, according to the type of dialysis provided. Design A retrospective analysis of the records of 31 patients with MHT. Setting A university-based, large tertiary-care hospital and its community-based satellite continuous ambulatory peritoneal dialysis (CAPD) clinics. Patients Only patients with renal failure caused by MHT and who were on dialysis between Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…Katz et al. (7) reported that 11/31 (36%) Black South Africans with malignant hypertension recovered sufficient renal function to discontinue dialysis after 150–365 d. A further four patients with malignant hypertension and ARF were able to stop dialysis after three months in the series reported by Yaqoob et al. (8).…”
Section: Discussionmentioning
confidence: 98%
“…Katz et al. (7) reported that 11/31 (36%) Black South Africans with malignant hypertension recovered sufficient renal function to discontinue dialysis after 150–365 d. A further four patients with malignant hypertension and ARF were able to stop dialysis after three months in the series reported by Yaqoob et al. (8).…”
Section: Discussionmentioning
confidence: 98%
“…Another striking finding is the fact that PD might delay the progression of advanced renal failure, preserving or improving RRF. [68][69][70][71][72][73] Actually, recovery of renal function sufficient to come off dialysis has been described in several reports of patients with interstitial nephritis 68 and malignant hypertension. 69 In an experimental model, PD retarded the progression of glomerular sclerosis in rats.…”
Section: Pd Versus Chronic Intermittent Hdmentioning
confidence: 99%
“…The three case reports, regarding patients who were all treated at a small dialysis Unit where a "tailor-made," highly personalized dialysis regimen is pursued, may offer a few ideas for discussion, in the context of the recent medical literature, that suggest that RFR, allowing discontinuation of dialysis, may occur more frequently than is generally believed. [13][14][15][16][17][18][19][20] While there is undoubtedly a quota of serendipity in the observation of a high prevalence of RFR in our series, linked to the small number of treated patients, this experience may suggest that small settings, which allow for a policy of highly personalized treatment, may be particularly suitable for enhancing kidney function recovery. Indeed, in our opinion, the individualized follow-up policy modulated the clinical decisions mainly on the basis of dialysis tolerance: we were quite reluctant to discontinue hemodialysis in our first patient, with good dialysis tolerance; conversely, in the other two patients, dialysis was withdrawn relatively early (i.e., when GFR was still below 10 mL/min) on account of poor tolerance to the dialysis sessions (Table 1).…”
Section: Discussionmentioning
confidence: 71%
“…[14][15][16][17] In other large series published since 2000, the incidence of RFR ranges from 2% to over 30%, the highest rates being recorded in severe hypertension and cholesterol emboli syndrome. [18][19][20] The definition of RFR is quite elusive, and the duration of dialysis after which kidney failure is considered as chronic ranges from 1 to 3 months. [14][15][16][17][18][19][20] Almost surprisingly, one of the clearest definitions of "chronic" dialysis stems from the studies on acute kidney injury: the RIFLE criteria define end-stage renal disease as the need for renal replacement therapy for more than 3 months.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation